The problem of food security in modern Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
The article describes one of the most important elements of the social functions of the state – food policy. The author explores the state of food security in modern Kazakhstan. Based on scientific analysis of legislation the author reveals the specific features of the legislative food security in modern Kazakh- stan. Analyzed the national interests of the Republic of Kazakhstan in the food sector. The main threats and risks associated with food security. To illuminate the problems stated in the article, the author of widely used methods for the analysis of legal acts that regulate food safety issues, comparative histori- cal, and other methods of scientific research. Analyzing the state of food security in modern Kazakhstan, the author came to the conclusion that to date in the field of study there are some serious problems that require adequate solutions. The author concludes that food security is an integral feature of the policy of the welfare state.
Keywords: social policy; the food sector; food; social and economic rights of the individual; the food problem; food security; food policy; the criteria of food security; food safety issues; food safety